2008
DOI: 10.1007/s12272-001-1154-0
|View full text |Cite
|
Sign up to set email alerts
|

Melanogenesis inhibitory compounds from Saussureae Radix

Abstract: Ten compounds were isolated from the EtOAc soluble part of the MeOH extract of Saussureae Radix, with their effects on melanin production also evaluated in B-16 mouse melanoma cell lines stimulated with 3-isobutyl-1-methylxanthine (IBMX), an elevator of cellular cAMP. The compounds were identified as aplotaxene (1), 1 beta-hydroxy arbusculin A (2), costunolide (3), dehydrocostuslactone (4), 11 beta,13-dihydrocostunolide (5), reynosin (6), heptadec-(9Z)-enoic acid (7), beta-sitosterol (8), linoleic acid methyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 27 publications
2
25
0
2
Order By: Relevance
“…It also reported that, costunolide is involved to inhibit the expression of inducible nitric oxide synthase (De Marino et al, 2005;Fukuda et al, 2001;Matsuda et al, 2000;Park et al, 1996) and the DNA-binding activity of NF-κB (Castro et al, 2000;Koo et al, 2001;Stefani et al, 2006) and has potential as natural herbicide (Macias et al, 1999). Furthermore, costunolide potentiated 1,25-(OH)2D3-induced differentiation in HL-60 promyelocytic leukemia cells (Choi et al, 2002b;Kim et al, 2008;Kim et al, 2002), via the interference with NF-κB activation. Further studies demonstrate that costunolide has antitumor potential by inhibiting proliferation, inducing apoptosis and reducing invasion and metastasis of a wide variety of tumor cells, including breast cancer cells (Bocca et al, 2004;Choi et al, 2005;Choi et al, 2011), hepatocellular carcinoma cells (Chen et al, 1995;Liu et al, 2011a;Sun et al, 2003), prostate cancer cells (Hsu et al, 2011), leukemia cells (Choi et al, 2002a;Choi and Lee, 2009;Choi et al, 2002b;Hibasami et al, 2003;Kanno et al, 2008;Kim et al, 2008;Kim et al, 2002;Kim et al, 2011b;Komiya et al, 2004;Lee et al, 2001;Song et al, 2001;Srivastava et al, 2006), gastric cancer cells (Ko et al, 2005;Rasul et al, 2011), colon cancer cells (Kawamori et al, 1995;Mori et al, 1994), melanoma cells (Chen et al, 2007;…”
Section: Biological Functionsmentioning
confidence: 97%
See 2 more Smart Citations
“…It also reported that, costunolide is involved to inhibit the expression of inducible nitric oxide synthase (De Marino et al, 2005;Fukuda et al, 2001;Matsuda et al, 2000;Park et al, 1996) and the DNA-binding activity of NF-κB (Castro et al, 2000;Koo et al, 2001;Stefani et al, 2006) and has potential as natural herbicide (Macias et al, 1999). Furthermore, costunolide potentiated 1,25-(OH)2D3-induced differentiation in HL-60 promyelocytic leukemia cells (Choi et al, 2002b;Kim et al, 2008;Kim et al, 2002), via the interference with NF-κB activation. Further studies demonstrate that costunolide has antitumor potential by inhibiting proliferation, inducing apoptosis and reducing invasion and metastasis of a wide variety of tumor cells, including breast cancer cells (Bocca et al, 2004;Choi et al, 2005;Choi et al, 2011), hepatocellular carcinoma cells (Chen et al, 1995;Liu et al, 2011a;Sun et al, 2003), prostate cancer cells (Hsu et al, 2011), leukemia cells (Choi et al, 2002a;Choi and Lee, 2009;Choi et al, 2002b;Hibasami et al, 2003;Kanno et al, 2008;Kim et al, 2008;Kim et al, 2002;Kim et al, 2011b;Komiya et al, 2004;Lee et al, 2001;Song et al, 2001;Srivastava et al, 2006), gastric cancer cells (Ko et al, 2005;Rasul et al, 2011), colon cancer cells (Kawamori et al, 1995;Mori et al, 1994), melanoma cells (Chen et al, 2007;…”
Section: Biological Functionsmentioning
confidence: 97%
“…Furthermore, costunolide potentiated 1,25-(OH)2D3-induced differentiation in HL-60 promyelocytic leukemia cells (Choi et al, 2002b;Kim et al, 2008;Kim et al, 2002), via the interference with NF-κB activation. Further studies demonstrate that costunolide has antitumor potential by inhibiting proliferation, inducing apoptosis and reducing invasion and metastasis of a wide variety of tumor cells, including breast cancer cells (Bocca et al, 2004;Choi et al, 2005;Choi et al, 2011), hepatocellular carcinoma cells (Chen et al, 1995;Liu et al, 2011a;Sun et al, 2003), prostate cancer cells (Hsu et al, 2011), leukemia cells (Choi et al, 2002a;Choi and Lee, 2009;Choi et al, 2002b;Hibasami et al, 2003;Kanno et al, 2008;Kim et al, 2008;Kim et al, 2002;Kim et al, 2011b;Komiya et al, 2004;Lee et al, 2001;Song et al, 2001;Srivastava et al, 2006), gastric cancer cells (Ko et al, 2005;Rasul et al, 2011), colon cancer cells (Kawamori et al, 1995;Mori et al, 1994), melanoma cells (Chen et al, 2007;Park et al, 2001b), cervical cancer cells (Sun et al, 2003), KB and P388 tumor cell (Mondranondra et al, 1990), and platinum-resistant human ovarian cancer cells . It was also reported that costunolide inhibited angiogenic response by blocking the angiogenic factor signaling pathway (Jeong et al, 2002) and microtubule-interactting activity of costunolide (Bocca et al, 2004).…”
Section: Biological Functionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Costunolide (1) and reynosin (100), isolated from Saussureae Radix, showed potent inhibitory effects on the IBMX-induced melanogenesis, in dose-dependent manners, with IC 50 values of 3 and 2.5 lg/mL, respectively (Choi et al, 2008). Costunolide (1) inhibited contractions of the aorta induced by KCl but exerted less effect on those induced by norepinephrine, indicating the possible Ca antagonistic action of costunolide.…”
Section: Other Activitiesmentioning
confidence: 99%
“…although surgery is important in the initial therapy of patients with breast or ovarian cancer, most patients require chemotherapy to eliminate any residual microscopic or macroscopic peritoneal implants. Human ovarian cancer cell lines appear to be sensitive to dehydrocostuslactone, suggesting it has anticancer activity (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%